PROBLEMATIKA IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN IPAS - Mutia, Nur Balqis; Admawati, Harsi (UIN AR-RANIRY, 2024)
This research was conducted to identify problems in the implementation of the Independent Curriculum in Natural and Social Sciences (IPAS) subject in an elementary school. A total of two teachers at SD Negeri 9 Kuala Langsa were selected as research subjects with purposive sampling techniques. Both teachers have been implementing the Merdeka Curriculum since the 2022/2023 school year. This research is descriptive qualitative research with interview questions and observation sheets as research instruments. The interview questions were used to explore information related to the problems of implementing the Merdeka Curriculum faced by educators in IPAS subject. In addition, information related to the process of learning preparation, implementation, and assessment was obtained through observation of documents, learning activities, and the school environment. The results showed that teachers faced problems in the implementation of the Merdeka Curriculum at the preparation, implementation, and assessment of learning stages. These problems can be overcome through regular meetings with teacher working groups, using effective learning strategies, and training on the implementation of the Merdeka Curriculum.